Analisis Dampak Kebijakan Insentif Fiskal terhadap Tingkat Komponen dalam Negeri (TKDN) Industri Manufaktur di Indonesia - Muhammad, Muhammad; Riyanto, Riyanto (UI Scholars Hub, 2025)
Over the last decade, the manufacturing sector's contribution to Indonesia's economy has declined. In 2010, it was 29.10% of GDP, but by 2022, it had dropped to 19.14%. Employment in the sector also fell, from 14.91% of the workforce in 2010 to 13.80% in 2022. To reverse this trend, the government introduced a policy to boost the Domestic Component Level (DCL) in manufacturing. By offering fiscal incentives to industries meeting certain DCL targets, the government aims to drive economic growth and job creation. A study using BPS data from 2008-2019 shows that this policy raised DCL by 23.5%.